Metody conjoint analysis a metody oparte na wyborach - Rybicka, Aneta (Conjoint Analysis Methods and Discrete Choice Methods, 2005)
In the paper are decompositional approach in measurement of consumers' preferences: conjoint analysis methods and discrete choice methods presented. Also are characteristic of this methods, their advantages and disadvantages and also their similarities and differences described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 462-470